Bis(7)-harmine derivatives as potential multi-target anti-Alzheimer agents - Du, Hongtao; Ma, Fang; Cao, Yuanyuan; Bai, Miaoyan; Gao, Xinyi; Yang, Ziyi; Xu, Yang; Yan, Yan (Frontiers in Chemistry, 2025)
IntroductionThe multi-targeted ligands (MTDL) strategy has been recognized as a promising Approach for the development of effective treatments against Alzheimer’s disease (AD), due to the presence of multiple pathological mechanisms in AD. In this study, a series of bis(7)-harmine derivatives were designed and synthesized as multifunctional drugs for the treatment of AD.MethodsThe derivatives were synthesized by chemical methods and their structure was confirmed by nuclear magnetic resonance (NMR). The Ellman’s assay was utilized to assess the inhibitory potential of derivatives against hAChE and hBuChE. The inhibitory activity of these derivatives on both hMAO-A and hMAO-B was assessed using a fluorescence-based method. The thioflavin T (Th-T) fluorescence assay was used to assess the inhibition of Aβ1−42 self-aggregation. The cytotoxicity was evaluated using the MTT assay. The Surflex-Dock program in Sybyl-X2.0 Software was employed for molecular docking.ResultsIn vitro studies revealed that numerous synthesized compounds exhibited potent inhibitory activity against hAChE, and hMAO-B (IC50 < 1 μM), as well as Aβ1−42 aggregation (IC50 < 20 μM). Importantly, the multitarget compounds 6d, 8c, and 8d exhibited remarkable efficacy in simultaneously mitigating Aβ-induced toxicity in SH−SY5Y cells while demonstrating minimal cytotoxicity. Furthermore, predicted ADMET results suggested that 6d, 8c, and 8d possessed favorable pharmacokinetic properties and demonstrated low toxicity levels. Additionally, molecular docking studies of 6d within the activesites of hAChE, hMAO-B, and Aβ1−42 elucidated the inhibition mechanism.Discussion and conclusionBased on these findings, it is evident that 6d, 8c, and 8d hold potential as promising multi-functional drugs for AD treatment.